2020
DOI: 10.1016/j.heliyon.2020.e05460
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison effects on brand addiction: A mediating role of materialism

Abstract: This research explores the role of materialism, and social comparison to brand addiction in relation to compulsive buying. A structural equation modeling was used to analyze data through partial least squares by collecting online data in Vietnam. The research findings explain social comparison is an antecedent leading to addictive behavior. Materialism mediates and increases the addictive behavior when consumers are significantly impacted by social comparison. In addition, brand addiction leads to word-of-mout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 94 publications
1
17
0
Order By: Relevance
“…(2021) , Pradhan et al. (2018) , and Le (2020) . Moreover, confidence was observed using five items based on Dash et al.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…(2021) , Pradhan et al. (2018) , and Le (2020) . Moreover, confidence was observed using five items based on Dash et al.…”
Section: Methodsmentioning
confidence: 96%
“…(2021) MAT2 I enjoy owning items that make others notice me. Le (2020) MAT3 I often worry about not being able to afford everything I want to buy. MAT4 My possessions reveal a great deal about how well I am doing in life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Bai et al (2021) found that brand passion, a component of brand love, directly influences brand addiction. Likewise, Le (2020, p. 1) argued that brand addiction “refers to consumers' addictive behavior, with consumers particularly loving the brand,” finding it associated with being a more intense but unhealthier relationship with a brand. Following these indications, we empirically assess the role of brand love as an antecedent of brand addiction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have focused on positive outcomes of brand addiction, such as increased word of mouth, willingness to pay a premium price (Le, 2020), brand exclusivity (Francioni et al , 2020) and improved self-esteem and life satisfaction (Mrad and Cui, 2020). Because brand addiction is an unhealthy relationship between a consumer and a brand, we are interested more in the effects it may have on negative consumer behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%